Neurosociology The Nexus Between Neuroscience and Social Psychology - Franks, David D.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Recently, neuroscientists have presented new research which has a direct impact on many areas of Social Psychology. In this innovative volume, the author explores the nexus of Social Psychology and Neuroscience with relation to: -The Human "Self" -The Social Nature of the Mind -Socialization and Language Acquisition -Role-Taking/Theory of Mind -Consciousness -Intersubjectivity -Balanced Social Constructionism -Human Agency -The Effect of Emotion on Rational Decision-Making This groundbreaking work integrates areas of George Herbert Mead's social behaviorism with current neuroscience. The chapters in this volume demonstrate how current work on mirror neurons supports the basic tenets of the American pragmatists' focus on the priority of motor behavior.
The Evolution of the Human Brain -- What Is Social About the Human Brain? -- The New Unconscious: Agency and Awareness -- Mirror Neurons: A Return to Pragmatism and Implications for an Embodied Intersubjectivity -- The Neuroscience of Emotion and Its Relation to Cognition -- The Self in Neuroscience and Social Psychology -- Consciousness, Quale, and Subjective Experience -- The Place of Imitation in Social Life and Its Anatomical Brain Supports -- Determinism and Free Will -- Conclusion.
Keywords: Social sciences; Neurosciences; Social Sciences; Sociology, general; Neurosciences